Analysis of Reward and Punishment System in Improving Productive Credit Analyst Performance with Transformational Leadership Support as Intervening Variable in Class A Branch Office of PT. Bank Nagari - Antonio, Youngky; Elfiswandi, Elfiswandi; Lusiana, Lusiana (Dinasti Publisher, 2025)
This study aims to test how much the analysis of the reward and punishment system in improving the performance of productive credit analysts with the support of transformational leadership as an intervening variable at the class A branch office of PT. Bank Nagari. The method of data collection through surveys and distributing questionnaires, with a sample of 67 respondents. The analysis method used structural equation modeling using smartpls. The results of the study obtained a significant effect of rewards on transformational leadership. There is a significant effect of punishment on transformational leadership. There is a significant effect of rewards on credit analyst performance. There is a significant effect of punishment on credit analyst performance. There is a significant effect of transformational leadership on credit analyst performance. There is a significant effect of rewards on credit analyst performance through transformational leadership. There is a significant effect of punishment on credit analyst performance through transformational leadership.